Impact of CD11c+ cells in conducting airway lumen on Aspergillus fumigatus conidia deposition in neutropenic mice - Pavelchenko, Mariia; Shalyapin, Svyatoslav; Portnov, Sergey; Bogorodskiy, Andrey; Bolkhovitina, Elena; Shevchenko, Vitalii; Sapozhnikov, Alexander; Borshchevskiy, Valentin; Shevchenko, Marina (Frontiers in Fungal Biology, 2025)
IntroductionInhaled conidia of the opportunistic fungi Aspergillus fumigatus settle in the airway mucosa and in alveolar spaces. Different immune cells typically provide crucial defense against fungal germination. However, in immunocompromised patients, the lack of sufficient pro-inflammatory immune response often leads to invasive aspergillosis, with current treatments being limited by insufficient understanding of the precise conidial distribution patterns in the airways.MethodsTherefore, we employed advanced imaging techniques, including immunohistochemistry, optical clearing, and confocal laser scanning microscopy, to map A. fumigatus conidial distribution in both immunocompetent and neutropenic mouse airways. We developed a 3D airway model distinguishing the main bronchus, intermediate bronchi, and terminal bronchioles, enabling quantitative analysis of conidial location. In addition, we analyzed the interactions of CD11c+ cells with conidia in the conducting airway mucosa.ResultsOur findings revealed that while the majority of conidia reached the alveolar space in both groups, neutropenic mice showed significantly higher conidial concentrations in bronchial branches, particularly in the main bronchus, compared with immunocompetent mice. Simultaneously, in the conducting airway mucosa of neutropenic mice, CD11c+ cells ingested an elevated number of conidia compared with immunocompetent mice.DiscussionThus, detailed mapping of the conidial distribution patterns provides crucial insights into the spatial aspects of antifungal treatment in neutropenic patients. The enhanced contribution of CD11c+ cells to conidial internalization in the conducting airway mucosa of neutropenic mice demonstrated in the present study emphasizes the potential of these cells in the development of more effective, cell-targeted antifungal treatments.